Fabrication of monolithic wheatstone bridge circuit for piezoresistive microcantilever sensor - Ab Rahim, Rosminazuin; Nordin, Anis Nurashikin; Abdul Malik, Noreha; Bais, Badariah; Majlis, Yeop Burhanuddin (2015)
In this paper, the fabrication of monolithic Wheatstone bridge circuit on piezoresistive microcantilever sensor is presented. The development of the device is realized through silicon micromachining technology on silicon substrate through three major fabrication steps including silicon piezoresistive microcantilever formation, aluminum deposition of Wheatstone bridge interconnections and microcantilever release. The electrical discontinuity of interconnections which is one of the major issues encountered in the fabrication process is discussed and analyzed. Deposition of proper thickness of metal interconnection layers through metal evaporation process accompanied with annealing process at low temperature ensures complete electrical connections in the monolithic Wheatstone bridge configuration. Measurement of the fabricated Wheatstone bridge circuit shows a good agreement between theoretical and experimental values indicating successful fabrication of the device. Fabrication of piezoresistive microcantilever structure integrated with monolithic Wheatstone bridge circuit with resistance values in the range of 1 to 9 kΩ has been successfully realized using silicon micromachining technology.